Coolitude: A geographer’s perspective - Reshaad Durgahee (Journal of Indentureship and its Legacies, 2023)
In this short essay, the author examines the influence of the concept of Coolitude on his understanding of the Indian indenture experience. Parallels between patterns of immigration are alluded to – whether the indentured immigration of the nineteenth and early twentieth century or post-colonial immigration from those sugar colonies of empire to their former metropoles. Coolitude’s recognition of the role of space and place is at the fore and the author asks us to take this into account in our exploration of the global indentured story, making the case for a more concentrated address of the geography of indenture.